2008
DOI: 10.1161/strokeaha.107.510107
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Cervicocephalic Artery Dissection

Abstract: Background and Purpose-Cervicocephalic artery dissection (CAD) after childbirth is rare. The objective of this study was to determine differences between postpartum and nonpostpartum CAD. Methods-We compared consecutive patients with postpartum CAD with a control group of women with nonpostpartum CAD. Results-Of 245 patients with CAD, 102 women Ͻ50 years (6 with postpartum CAD and 96 with nonpostpartum CAD) were identified. Vascular risk factors and presenting characteristics did not differ significantly betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(119 citation statements)
references
References 14 publications
2
106
0
8
Order By: Relevance
“…Occurrence of arterial dissection has been observed by others in a minority of cases with cSAH though a direct causal relationship has not been established. 6,13,26 It is possible that edema of arterial wall and sudden surges in blood pressure predisposes to dissection.…”
Section: Recurrent Hemorrhage (Intracerebral Hemorrhage)mentioning
confidence: 99%
“…Occurrence of arterial dissection has been observed by others in a minority of cases with cSAH though a direct causal relationship has not been established. 6,13,26 It is possible that edema of arterial wall and sudden surges in blood pressure predisposes to dissection.…”
Section: Recurrent Hemorrhage (Intracerebral Hemorrhage)mentioning
confidence: 99%
“…Although we did not find clinical evidence for sympathetic activation in our patient, the lack of Horner's syndrome would support this hypothesis. An association between RCVS and unilateral CAD has been noted in single case reports (3)(4)(5). However, in all of them concomitant more common causes of RCVS were present.…”
Section: Discussionmentioning
confidence: 87%
“…Carotid artery dissection (CAD) has been discussed as a rare possible cause. So far, only single cases of unilateral CAD and RCVS have been reported, although all of them in combination with other more common causes, such as exposure to vasoactive substances or postpartum period (3)(4)(5). Herein, we describe a patient with spontaneous bilateral CAD and concurrent RCVS.…”
Section: Introductionmentioning
confidence: 94%
“…Dissection is much more common in extracranial segments of the carotid than it is in vertebral arteries. The most preferred site for intracranial carotid artery dissection is the supraclinoid segment beyond the origin of the ophthalmic artery, with or without extension to the MCA or ACA (3,16). It was observed that CCAD occurred more commonly in older child-bearing females and had a mean age of onset of 33,7 years (5-15) ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Unilateral headache and contralateral weakness are the most common neurological symptoms at the onset of disease. Generally, neurological symptoms appear within the first 24 hours but may occur later (3,24). The most common clinical presentations of CCAD are stroke or TIA, and intracranial haemorrhage is less common (4).…”
Section: Discussionmentioning
confidence: 99%